Desain dan Implementasi Inverter Satu Fasa 400 Watt dengan Metode Switching High Frequency - Jauhar Ismiyadinata; Harry Yuliansyah; Muhammad Reza Kahar Aziz; Arief Syaichu Rohman (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
This article proposes a design of 400 watt inverter with frequency of 50 Hz at voltage of 12 Vdc input and 220 Vac output. This inverter is designed to convert the Direct Current (DC) into Alternating Current (AC) voltage with the purpose to utilize DC electricity generated by renewable energy. Hence, the energy can be employed as the replacement of the commercial electricity. In this research, the inverter is designed with the use of Switching High Frequency (SHF) method as the amplifier system applied for step up input voltage. Besides, the proposed inverter also utilizes the Sinusoidal Pulse Width Modulation (SPWM) method as the driver resulting the output signal in the form of pure-sine-wave. Furthermore, the switching system for SHF method in this research employs Arduino nano as the control and EGS002 as the SPWM driver. To obtain the real data, the examination is performed with connecting the inverter directly to the load, e.g., bulb, fan, and solder. Finally, the examination and analysis of the implementation result confirm that the design works well and fulfills the expected specification. Hence, this inverter design can be expected to provide the scientific contribution and applied for renewable energy especially in Indonesia, and generally in the world. Keywords: Arduino, DC-AC Inverter, SHF, Solar Cell, SPWM